Comparison of oral absorption models for pregabalin: usefulness of transit compartment model - Hong, Taegon (Drug Des Devel Ther, 2016)
Pregabalin is an anticonvulsant used for the treatment of neuropathic pain and partial seizure in adults. The aim of this study was to develop a population pharmacokinetic (PK) model to describe the absorption characteristics of pregabalin given fasted or after meals. Data from five healthy subject PK studies (n=88) of single- or multiple-dose pregabalin (150 mg) were used. Pregabalin was administered twice daily, without meals or 30 min after a meal (regular or high-fat diet) in the morning and 30 min or 4 h after a meal (regular diet) in the evening. Serial plasma samples were collected up to 24 h after the last dose for PK analysis. Because the peak concentrations were not properly modeled by a conventional first-order absorption model, Erlang frequency distribution, Weibull-type absorption, and transit compartment models were tested on a two-compartment linear PK model using a nonlinear mixed-effects method (NONMEM; version 7.3). The transit compartment model best described the absorption characteristics of pregabalin regardless of meal status. We conclude that the absorption model should be carefully chosen based on the principle of model development and validation and not by following a conventional first-order absorption model for its popularity and simplicity, especially when the PK dataset includes densely sampled absorption-phase data.